A Pilot Study of Mesenchymal Stem Cell Therapy for Acute Liver Allograft Rejection. (26th November 2017) - Shi, Ming; Liu, Zhenwen; Wang, Ying; Xu, Rounan; Sun, Yanling; Zhang, Min; Yu, Xi; Wang, Hongbo; Meng, Lingzhan; Su, Haibin; Jin, Lei; Wang, Fu‐Sheng
Abstract: Acute allograft rejection remains common after liver transplantation despite modern immunosuppressive agents. In addition, the long‐term side effects of these regimens, including opportunistic infections, are challenging. This study evaluated the safety and clinical feasibility of umbilical cord‐derived mesenchymal stem cell (UC‐MSC) therapy in liver transplant patients with acute graft rejection. Twenty‐seven liver allograft recipients with acute rejection were randomly assigned into the UC‐MSC infusion group or the control group. Thirteen patients received one infusion of UC‐MSCs (1 × 10 6 /kg body weight); one patient received multiple UC‐MSC infusions; 13 patients were used as controls. All enrolled patients received conventional immunosuppressive agents with follow‐up for 12 weeks after UC‐MSC infusions. No side effects occurred in treated patients. Four weeks after UC‐MSC infusions, alanine aminotransferase levels had decreased markedly and remained lower throughout the 12‐week follow‐up period. Importantly, allograft histology was improved after administration of UC‐MSCs. The percentage of regulatory T cells (Tregs) and the Treg/T helper 17 (Th17) cell ratio were significantly increased 4 weeks after infusions; in contrast, the percentage of Th17 cells showed a decreasing trend. In controls, the percentages of Tregs and Th17 cells and the Treg/Th17 ratio were statistically unchanged from the baseline measurements. Transforming growth factor beta 1 and prostaglandin E2 were increased significantly after UC‐MSC infusions; by contrast, there were no significant changes in controls. Our data suggest that UC‐MSC infusion for acute graft rejection following liver transplantation is feasible and may mediate a therapeutic immunosuppressive effect. Stem Cells Translational Medicine 2017;6:2053–2061 Abstract : Liver transplant patients with acute graft rejection received the UC‐MSCs infusion (A). Four weeks after UC‐MSC infusions, ALT levels had decreased markedly and remained lower throughout the 12 week follow‐up period (B). The Treg/Th17 ratio was significantly increased 4 weeks after infusions; whereas in controls, the Treg/Th17 ratio was statistically unchanged from the baseline measurements (C). Abbreviations: ALT, alanine aminotransferase; Th17, T helper 17; Treg, regulatory T cell; UC‐MSC, umbilical cord‐derived mesenchymal stem cell.